Reformation of the surface oceanic circulation during Paleogene: Calcareous nannoplanktonic, foraminiferal and oxygen isotopic evidences - Ushakova, Maola; Blyum, Natalia (Ediciones Universidad de Salamanca (España), 1995)
[EN] Paleogene calcareous nannoplankton evolution with regard to morphotype changes was analysed. The^°0/1"0 ratio in planktonic foraminifera tests was studied. Conclusions about surface water temperature and salinity changes and about main features of surface circulation based on these data were arrived. Can be seen that the reformation from the mainly halinotypic circulation of the early Paleogene into halotherme one took place in the middle Eocene. In the same time the notable climatic zonation appeared. In connection with the beginning of Antarctic glaciation and climatic cooling during the late Eocene and Oligocène existed mixed halotherme - thermohalinic circulation. Since the middle of Miocene the thermotypic circulation became increase. [ES] Se analiza la evolución del nannoplancton calcáreo paleógeno, especialmente sus cambios morfotípicos. Se estudia la relación l°O/l"0 en las conchas de foraminíferos planctónicos. Se obtienen conclusiones sobre cambios de temperatura del agua superficial y de salinidad y algunas características de la circulación superficial. Parece que el cambio, desde la circulación principalmente halinotópica del Paleógeno inferior a la halotérmica, tuvo lugar en el Eoceno medio. En ese tiempo aparece una marcada zonación climática. Coincidiendo con el comienzo de la glaciación antartica y el enfriamiento climático, durante el Eoceno superior y el Oligoceno, se dio una combinación de circulaciones halotérmica - termohalina. Hacia la mitad del Mioceno se incrementa la circulación termotípica.